As condições de trabalho na área de saúde e o processo de adoecimento da (o) assistente social - Camara, Patricia Cristiane Soares (2013)
The requirements in the world of work in the contemporary impact on quality of life, health workers in their relations with users and other professionals of the healthcare team. Given this reality, this study discusses the working conditions in health and disease process of (a) having social goals as analyze the implications of working conditions in the disease (the) social workers in state hospitals Metropolitan Region Christmas (NMR); identify the main diseases affecting social workers in hospitals in the SESAP NMR and reveal the relationship between the disease processes of social and working conditions in hospitals in the state NMR. The research was guiding questions to reveal how to configure the work, conditions of work and of the disease process (the) social worker. To grasp the socioeconomic profile of (the) social workers, the characterization of the work, duties and responsibilities in the sociooccupational, factors that interfere with the disease process of (the) social workers of RMN, and actions and investments Policy on Occupational Health RN correlating to illness today is that we set for the unveiling of the movement of the object of study through the methodological approach with documentary research aimed at literature review; extensive direct observation correlated to real life observation and application of 66 (sixty-six) questionnaires. The data from the closed questions were treated using the Statistical Package for the Social Sciences (SPSS). The open questions were transcribed and then analyzed the light of theoretical work on the subject. The research reveals that social workers are subject to conditions and labor relations precarious illness causing health problems because some of these professionals, among them are: stress, allergies and skin conditions or, Read / WMSD among other diseases. Thus, we understand the need for debates about the relationship work (the) social worker and worker health before the contradictions of capital also present in public health services